The first polynomial is:
-3x³ + 2x – 5
Then we add a polynomial p(x) and we get:
-3x³ + 2x – 5 + p(x) = 4x³ + 7x² – 3
We will find that p(x) = 7x³ + 7x² - 2x + 2
Now let's see how we got it:
Notice that the degree of the polynomial does not change, so p(x) is a polynomial of degree 3.
Then we can write:
p(x) = ax³ + bx² + cx + d
Then we have:
-3x³ + 2x – 5 + ( ax³ + bx² + cx + d) = 4x³ + 7x² – 3
(-3 + a)x³ + bx² + (2 + c)x + (-5 + d) = 4x³ + 7x² – 3
Notice that the above inequality should work for every value of x, so the terms with the same exponent must be equal between them:
(-3 + a)x³ = 4x³
bx² = 7x²
(2 + c)x = 0
(-5 + d) = – 3
Now we can remove the variables in all of these equations to get:
(-3 + a) = 4
b = 7
(2 + c) = 0
(-5 + d) = – 3
Now we can solve all of these and find the coefficients of our polynomial p(x).
-3 + a = 4
a = 4 + 3 = 7
a = 7
b = 7
2 + c = 0
c = -2
-5 + d = -3
d = -3 + 5 = 2
d = 2
Then we have:
p(x) = 7x³ + 7x² - 2x + 2
If you want to learn more, you can read:
https://brainly.com/question/11536910